2019
DOI: 10.5194/acp-2019-7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhanced ice nucleation activity of coal fly ash aerosol particles initiated by ice-filled pores

Abstract: <p><strong>Abstract.</strong> Ice-nucleating particles (INPs), which are precursors for ice formation in clouds, can alter the microphysical and optical properties of clouds, hence, impacting the cloud lifetimes and hydrological cycles. However, the mechanisms with which these INPs nucleate ice when exposed to different atmospheric conditions are still unclear for some particles. Recently, some INPs with pores or permanent surface defects of regular or irregular geomet… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 60 publications
(75 reference statements)
2
5
1
Order By: Relevance
“…This is also consistent with recent results of Umo et al. (2019), who showed that CFA can form ice via PCF at T < HNT . Additionally, a clear distinction is visible for all cirrus temperatures investigated here, suggesting an intrinsic difference in ice nucleation ability depending on dry‐ or wet‐generation of the CFA particles.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…This is also consistent with recent results of Umo et al. (2019), who showed that CFA can form ice via PCF at T < HNT . Additionally, a clear distinction is visible for all cirrus temperatures investigated here, suggesting an intrinsic difference in ice nucleation ability depending on dry‐ or wet‐generation of the CFA particles.…”
Section: Resultssupporting
confidence: 93%
“…The absence of ice nucleation below water saturation at T = 243 K for the cloud processed CFA samples, seems to be in conflict with the temperature‐cycling measurements of Umo et al. (2019), who report an ice nucleation activity of CFA particles as warm as 263 K for the first time after they had been temperature‐cycled to T ≈ 228 K. Umo et al. (2019) concluded that a few temperature‐cycled CFA particle types can contain ice‐filled pores that cause the improved ice formation through preactivation.…”
Section: Resultscontrasting
confidence: 80%
See 3 more Smart Citations